CONTRACTORS’ PERCEPTIONS OF LATE PAYMENTS - R CUMBERLEGE; B BOTHA; M BENTLEY (Journal of Construction Project Management and Innovation)
The purpose of this article is to identify the effects of late payments on contractors, and to implement procedures which will ultimately eliminate payment delays in future. The article also highlights the importance of understanding the mechanisms and the workings of various contract agreements, in order for the contractor to be aware of their rights and responsibilities in terms of the contract, as well as what legal steps could be taken should a client be in default regarding payment. A quantitative research method was used. A structured questionnaire was administered to contractors who are members of the Master Builders Association (MBA), Eastern Cape Province. The findings revealed that contractors’ cash flow is greatly affected as a result of late payments. Smaller contractors even face bankruptcy. Contractors are also forced to suspend work on-site due to late payments; this extends the contract period, and, as a result, the contractor’s expenses increase. It is also suggested that payment legislation should be introduced in order to reduce the number of late payments made by clients to contractors. The research is limited to contractors who are registered members of the Master Builders Association (MBA), Eastern Cape Province. An understanding of the effects of late payments will assist contractors in the smooth running of a construction project financially. Contractors will also benefit from being knowledgeable in terms of contractual agreements in the event of a delay in payment from the client. Contractors will furthermore be able to identify the effects of late payments, and will be able to plan accordingly.